TAKHRIJ HADITH CHAPTERS 1-3 IN THE BOOK OF TA'LIMUL MUTA'ALLIM - Shalihah, Raadliyatush; Hamzah, Muhammad Habibi (Tsaqofah : Jurnal Pendidikan Islam, 2022)
Ta'limul Muta'allim is a book that is widely studied by knowledge seekers. In the book, Az-Zarnuji also included the Prophet's hadith as an amplification of his explanation. So this research was conducted to mentakhrij the traditions in chapters 1-3 in the book of Ta'limul Muta'allim by using the Takhrij bil Lafdzi method. After doing takhrij, it can be found that the hadith in chapter 1 is in Sunan Ibn Majah, the second chapter is in Sahih Bukhari and Shu'abul Iman, the third chapter hadith is in Sahih Bukhari. Keywords: Ta'limul Muta'allim, method of takhrij hadiths